Online Pharmacy Education: Challenges and Perceptions from an Academic Perspective - I Gusti Ayu Rai Widowati; Ida Ayu Manik Partha Sutema; Ni Putu Aryati Suryaningsih (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2025)
The digitalization of education is reshaping pharmacy instruction through the integration of online learning systems. While the adoption of digital learning continues to grow, research on the perceptions, readiness, and challenges faced by students and faculty in Indonesia remains limited. Understanding these factors is essential for formulating effective strategies in online education. This study investigates the perceptions, readiness, and obstacles encountered by pharmacy students and faculty at Bali International University in relation to online education. It further explores barriers to digital learning and their impact on development needs. Employing a sequential explanatory mixed-methods design, the study first gathered quantitative data, followed by qualitative insights through in-depth interviews. A total of 329 respondents participated in the research. The quantitative results revealed no significant association between readiness (OR = 0.957, 95% CI = 0.869–1.055, p = 0.399) or attitude (OR = 1.059, 95% CI = 0.929–1.207, p = 0.364) and development needs. However, barriers showed a statistically significant correlation with development (OR = 1.777, 95% CI = 1.066–2.964, p = 0.027). Qualitative data, analyzed using a thematic framework, identified five central themes: accessibility, collaboration, ICT utilization, professional development, and the broader implications of digitalization in pharmacy education. This study underscores the transformative potential of digital technology and the importance of addressing existing challenges to enhance the quality and accessibility of pharmacy education. These improvements are vital to equipping future pharmacists with the competencies required to thrive in global healthcare systems and effectively contribute to integrated pharmacy services worldwide.